Feasibility of novel rear-side mirage deflection method for thermal conductivity measurements - Kim, Gwantaek; Kim, Moojoong; Kim, Hyunjung (Sensors, 2021)
Among the noncontact measurement technologies used to acquire thermal property information, those that use the photothermal effect are attracting attention. However, it is difficult to perform measurements for new materials with different optical and thermal properties, owing to limitations of existing thermal conductivity measurement methods using the photothermal effect. To address this problem, this study aimed to develop a rear-side mirage deflection method capable of measuring thermal conductivity regardless of the material characteristics based on the photothermal effect. A thin copper film (of 20 μm thickness) was formed on the surfaces of the target materials so that measurements could not be affected by the characteristics of the target materials. In addition, phase delay signals were acquired from the rear sides of the target materials to exclude the influence of the pump beam, which is a problem in existing thermal conductivity measurement methods that use the photothermal effect. To verify the feasibility of the proposed measurement technique, thermal conductivity was measured for copper, aluminum, and stainless steel samples with a 250 μm thickness. The results were compared with literature values and showed good agreement with relative errors equal to or less than 0.2%.
Keywords: Material characteristics; Measurement techniques; Mirage deflection; Noncontact measurements; Optical and thermal properties; Photothermal effects; Thermal conductivity measurements; Thin copper films; Light absorption thin film; Phase delay; Photothermal effect; Rear-side mirage method; Thermal conductivity; Thermal properties